Strategi Komunikasi Humas Dalam Membangun Citra Perusahaan Melalui Edukasi Digital Skul.id Pada Telkomsel Branch Medan - Muhammad Rifai Saragih; Faustyna Faustyna (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2026)
This study aims to determine the public relations communication strategy in building a corporate image through the Skul.id digital education program at Telkomsel Branch Medan. This research is motivated by the importance of the role of public relations in building a corporate image through the use of digital media, especially in the context of digital transformation in the field of education. The research method used is a qualitative approach with a descriptive research type. Data collection techniques were carried out through interviews, observations, and documentation. Informants in this study were internal parties at Telkomsel Branch Medan who were directly involved in the implementation of the Skul.id program. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results showed that the public relations communication strategy of Telkomsel Branch Medan in the Skul.id program applies the Grunig and Hunt communication model, namely publicity, public information, two-way asymmetrical, and two-way symmetrical. This strategy was carried out through the use of digital media such as social media and websites, as well as direct approaches through socialization, workshops, and school visits. In addition, Telkomsel also conducts two-way communication by collecting feedback from users as material for program evaluation. The Skul.id program has proven to have a positive impact on the company's image, where Telkomsel is perceived not only as a telecommunications service provider but also as a company supporting the digitalization of education. In this study, the company's image was formed through the direct experiences of program users. Therefore, an integrated PR communication strategy oriented toward user experience plays a crucial role in building a company's image in the digital era.